Efficient Preparation of Rare Earth Oxides from Back Extraction Praseodymium Neodymium Chloride by Flash Pyrolysis. Issue 20 (23rd May 2022) - Lei, Xiang; Wang, Houqing; Fu, Liwen; Wang, Jinliang; Xu, Shengming
Abstract: Praseodymium‐neodymium‐oxide powder was prepared using a simple citric acid‐assisted ultrasonic spray pyrolysis. The rare‐earth oxide transformation process and temperature were clarified using the characterisation results. The results show that a sufficient mass ratio of citric acid can promote the decomposition of chlorine oxides produced during calcination. This favourable change is attributed to the unique composition and morphology of the precursors. Furthermore, the residual chlorine content and migration behaviour in the praseodymium‐neodymium‐oxide powder were studied and discussed. This study provides the necessary theoretical and experimental basis for the application of ultrasonic spray pyrolysis technology for rare‐earth oxide production. Abstract : Low residual chlorine praseodymium neodymium oxide powder products were obtained through citric acid assisted spray pyrolysis combined with low temperature calcination process. In this process, the reduction principle of calcination temperature, the migration law of residual chlorine and the phase transformation mechanism during calcination were studied in detail. The results are beneficial to promote the application of spray pyrolysis process in the production of rare earth oxides.